Efficacité du tutorat et étude des profils « efficaces » des tutorés - Sandoss Ben Abid-Zarrouk; Marc Weisser (Recherches en Éducation)
Tutoring is a methodological device which has goal to improve successful rates of university's undergraduate, primarily for new entrants. The purpose of this contribution is to show the effectiveness of this device. This is from a survey conducted in two stages in the University of Haute Alsace (UHA) that we are able to demonstrate initially that students who followed the tutoring are more likely to pass in second year and that students who choose the tutoring from the perspective of success are more likely to get their L1 compared to those who come seeking a methodological contribution.